2012
DOI: 10.3109/09553002.2012.666005
|View full text |Cite
|
Sign up to set email alerts
|

Single-strand DNA breaks in human hair root cells exposed to mobile phone radiation

Abstract: A short-term exposure (15 and 30 min) to RFR (900-MHz) from a mobile phone caused a significant increase in DNA single-strand breaks in human hair root cells located around the ear which is used for the phone calls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…In the following years, Ji et al studied the health impact of 4-hour acute exposure to commercially available mobile phones on certain parameters such as an indicator of DNA damage in 14 healthy adult volunteers, and concluded that this type of electromagnetic radiation was capable to trigger DNA damage in lymphocytes in vivo (29). More recently, Çam et al analysed the short-term effects of radiofrequency radiation exposure on single-strand DNA breaks in 8 healthy human subjects before and immediately after exposure to a 900-MHz GSM mobile phone for 15 and 30 min (30). Interestingly, talking on a mobile phone for up to 30 min significantly increased single-strand DNA breaks in cells of hair roots close to the phone, a damage that was found to be the highest after 30 min of phone use.…”
Section: Resultsmentioning
confidence: 99%
“…In the following years, Ji et al studied the health impact of 4-hour acute exposure to commercially available mobile phones on certain parameters such as an indicator of DNA damage in 14 healthy adult volunteers, and concluded that this type of electromagnetic radiation was capable to trigger DNA damage in lymphocytes in vivo (29). More recently, Çam et al analysed the short-term effects of radiofrequency radiation exposure on single-strand DNA breaks in 8 healthy human subjects before and immediately after exposure to a 900-MHz GSM mobile phone for 15 and 30 min (30). Interestingly, talking on a mobile phone for up to 30 min significantly increased single-strand DNA breaks in cells of hair roots close to the phone, a damage that was found to be the highest after 30 min of phone use.…”
Section: Resultsmentioning
confidence: 99%
“…This was 6-7 hours of cell phone usage per day. On review of literature we found an interesting study showing single-strand DNA breakage in human hair root cells exposed to mobile phone radiation [13]. According to the study these changes are temporary and normal healthy cells are capable of complete recovery from such effects [13].…”
Section: Observations and Resultsmentioning
confidence: 99%
“…On review of literature we found an interesting study showing single-strand DNA breakage in human hair root cells exposed to mobile phone radiation [13]. According to the study these changes are temporary and normal healthy cells are capable of complete recovery from such effects [13]. The patient was advised to reduce cell phone conversation time, use hands free option instead of holding the phone to the ear and follow the hair care program for protection of hair and stimulation of hair growth.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…1,4,5 More specifically, it has been reported that cell phone radiofrequency can damage DNA and deregulate gene expression of apoptotic and antiapoptotic pathways, including signal transducer and activator of transcription 3 (STAT3), tumor necrosis factor a, and interleukin-6 in brain cells. [6][7][8][9] On the other hand, it has been shown that these genes can play an important role in the progression of several types of human carcinomas via the initiation of the epithelial-mesenchymal transition event. 10 Nevertheless, there is no study about the outcome of cell-phone radiofrequency on human cancers' progression, including head and neck malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several studies suggested an association between cell phone use and the development of brain cancer, especially glioma. 1,4,5 On the other hand, it has been reported that cell-phone radiofrequency can damage DNA and deregulate several genes related to this event and epithelial-mesenchymal transition in brain cell models, [6][7][8][9] which is a hallmark of cancer progression. 10 All of this implicates cell-phone radiofrequency in human cancer initiation and/or progression especially in specific parts of the human body, such as the head and neck.…”
Section: Introductionmentioning
confidence: 99%